A STUDY ON POVERTY ATTRIBUTIONS AND SUBJECTIVE WELL-BEING AMONG LOW INCOME GROUP: COMPARISON BETWEEN SUBURBAN AND RURAL AREAS OF MALAYSIA - Ismail, Rozmi (International Journal of Psychosocial Rehabilitation, 2020)
Although the concepts of attribution is widely used in social psychology, little is known about the relationships between this concepts towards the subjective well-being of the low-income group. This study examines how poverty attributions contribute to the subjective well-being of low income group in Malaysia. In this paper, we hypothesized that how people define the causes of poverty will affect their subjective well-being. We also hypothesized that these factors will differ according to urbanized status of the sampled population. A total of 384 respondents in suburban area in Kuala Lumpur and rural area in Pahang participated in this survey. The findings showed that the respondents mostly attributed poverty to micro-environmental factors (e.g. low income) and fatalistic factors (e.g. having many children to support). There were also significant differences of these poverty attributions between suburban and rural respondents. The multivariable analysis results showed significant associations between several types poverty attributions (micro-environmental, individualistic and fatalistic) and subjective well-being among the respondents. There were consistent significant associations between fatalistic attribution and well-being, even after the data was separately analyzed according to locality (rural vs. suburban). This study implies that poverty attribution is a crucial variable in explaining the mindset and subjective well-being of the general population of Malaysia, especially for the low-income group.